Promising Links between Meditation and Reduced (Brain) Aging: An Attempt to Bridge Some Gaps between the Alleged Fountain of Youth and the Youth of the Field - Kurth, Florian; Cherbuin, Nicolas; Luders, Eileen (Frontiers in Psychology, 2017)
Over the last decade, an increasing number of studies has reported a positive impact of meditation on cerebral aging. However, the underlying mechanisms for these seemingly brain-protecting effects are not well understood. This may be due to the fact, at least partly, that systematic empirical meditation research has emerged only recently as a field of scientific scrutiny. Thus, on the one hand, critical questions remain largely unanswered; and on the other hand, outcomes of existing research require better integration to build a more comprehensive and holistic picture. In this article, we first review theories and mechanisms pertaining to normal (brain) aging, specifically focusing on telomeres, inflammation, stress regulation, and macroscopic brain anatomy. Then, we summarize existing research integrating the developing evidence suggesting that meditation exerts positive effects on (brain) aging, while carefully discussing possible mechanisms through which these effects may be mediated.